Computer modelling and simulation of a bioreactor for tissue engineering - Pereira, Rúben F.; Freitas, Dino; Tojeira, Ana; Almeida, Henrique A.; Alves, Nuno; Bártolo, Paulo J. (International journal of computer integrated manufacturing, 2014)
A conventional approach to tissue engineering involves the implantation of porous, biodegradable and biocompatible scaffolds seeded with cells into the defect site. In some strategies, tissue engineering requires the in vitro culture of tissue-engineering constructs for implantation later. In this case, bioreactors are used to grow 3D tissues under controlled and monitored conditions. However, the quality of the resulting 3D tissue is highly dependent on the design and dimensions of the bioreactor, as well on the operating conditions. In this work, a computational fluid dynamic software package was used to investigate the influence of cylindrical bioreactor dimensions (length and diameter) on the fluid flow and scaffold shear stress. Computer simulations were performed using three different rotational movements (horizontal, vertical and biaxial rotation) and appropriate boundary conditions. Results show that the effect of the bioreactor length on the scaffold shear stress is more important than the diameter, while high length is associated to low scaffold shear stress. On the other hand, the fluid flows within the bioreactor and scaffold shear stresses are dependent on the rotational movement, being more uniform in the biaxial rotation due to the combination of rotational movements.